Dynamic traffic signalling based on the density of vehicle traffic in urban areas using data analysis techniques - VinaySai Kumar, P; Mohammed Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
With the advent of the urban population,the need for effectivetraffic management has taken its prominence. There are many studies with various typesof solutions. Our study focuses on how the time can be reduced based on the traffic density in that area and the previous area. The present scenario is an acutesystem of traffic lights, so our proposal is based on the analysis of previous junction timer and the traffic lights will adaptdepending on traffic conditions. The machine learning techniques like reinforcement learning are being used to reduce commute time and will save the humans fromlethal pollution. This will eventually increase the life span of the humans.Â Â